Posing problems using Cabri - Engström, Lil; Lingefjärd, Thomas (NOMAD Nordic Studies in Mathematics Education, 2007)
The purpose of Engström’s research was to investigate in which ways and to what extent three different teachers, one in Switzerland and two in Sweden, used a specific dynamical geometry software, Cabri Géomètre, in upper secondary school. The method consisted mainly of field notes and audio recording during observations in classrooms. The field research was then analysed and evaluated according to the following questions: a) How do teachers pose problems and b) how do teachers make students’ experiences useful when Cabri Géomètre is accessible? The result showed that one important factor enabling to challenge the pupils in learning mathematics when using Cabri Géomètre is the way the teacher poses the problems or the questions. The word ’challenging’ means among other things, that the pupils continue asking themselves questions so that there will be continuous learning, not limited to finding just one correct answer.